Essential oils from plants of the genus Cymbopogon as natural insecticides to control stored product pests. (May 2015) - Hernandez-Lambraño, Ricardo; Pajaro-Castro, Nerlis; Caballero-Gallardo, Karina; Stashenko, Elena; Olivero-Verbel, Jesus
Abstract: The repellent and fumigant activities of essential oils (EOs) isolated from plants of the Cymbopogon genus against adults of Oryzaephilus surinamensis (L.) and Sitophilus zeamais Motsch were investigated. Cymbopogon martinii was the most toxic EO with LC50 values of 37.2 and 159 μL/L air for O. surinamensis and S. zeamais, respectively. Cymbopogon nardus EO showed greatest repellent activity with RC50 values of 0.03 and 0.04 μL/cm 2, respectively, for examined pests. All oils were more effective as repellents than the commercial product IR3535, and O. surinamensis was more sensitive than S. zeamais to the EOs. These results suggest that EOs isolated from plants of the genus Cymbopogon can play an important role in stored grain protection and reduce the risks associated with the use of synthetic insecticides. Highlights: Cymbopogon oils were tested on Oryzaephilus surinamensis and Sitophilus zeamais. Cymbopogon nardus essential oil showed the best repellent properties. O. surinamensis was more sensitive than S. zeamais to the essential oils. Essential oils were better repellents than the commercial product IR3535.